Réponses

2014-05-10T15:16:01+02:00
 A(X)= (9-4x²)(2x+6)-(3-x)(9-4x²)
a = 18x + 54 -8xau cube -24x² - (27 -12x² -9x +4x au cube
a = 18x +54 -8xau cube -24x² -27 +12x² +9x -4x au cube
a =  -12x au cube  -12x² +27x  +27
x² fois x = x au cube car je ne sais plus
  • Utilisateur Brainly
2014-05-10T15:46:56+02:00
Bonjour, 

Développer et réduire:

A(X)= (9-4x^2)(2x+6)-(3-x)(9-4x^2)  \\ =18x+54-8x^3-24x^2-(27-12x^2-9x+4x^3) \\ =18x+54-8x^3-24x^2-27+12x^2+9x-4x^3 \\ =-12x^3-12x^2+27x+27

Bonne continuation! =)